2001
DOI: 10.1152/ajpheart.2001.280.6.h2563
|View full text |Cite
|
Sign up to set email alerts
|

Persistence of gap junction communication during myocardial ischemia

Abstract: During myocardial ischemia, severe ATP depletion induces rigor contracture followed by intracellular Ca2+ concentration ([Ca2+]i) rise and progressive impairment of gap junction (GJ)-mediated electrical coupling. Our objective was to investigate whether chemical coupling through GJ allows propagation of rigor in cardiomyocytes and whether it persists after rigor development. In end-to-end connected adult rat cardiomyocytes submitted to simulated ischemia the interval between rigor onset was 3.7 +/- 0.7 s, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
61
0

Year Published

2003
2003
2009
2009

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(61 citation statements)
references
References 45 publications
0
61
0
Order By: Relevance
“…However, recent studies (19,27) have shown that chemical coupling via the gap junction is main- Fig. 6.…”
Section: Physical Interaction Of Cx43 With Protein Kinases During Myomentioning
confidence: 99%
“…However, recent studies (19,27) have shown that chemical coupling via the gap junction is main- Fig. 6.…”
Section: Physical Interaction Of Cx43 With Protein Kinases During Myomentioning
confidence: 99%
“…Assessment of GJIC activity in heart sections was performed using the method described by Ruiz-Meana et al 25 with a modification. Briefly, after 30 min of LAD occlusion and EB infusion, a thick transverse section was excised between the LAD ligature and the apex.…”
Section: Dye Transfer Assay In Heart Sectionsmentioning
confidence: 99%
“…To confirm that the concentrations of 0.5 mM heptanol and, importantly, 6 M Gap 27 administered in protocol 2 inhibited gap junctions/hemichannels in normoxic myocardium (i.e., the conditions under which D-myo-IP 3 was administered and initiated protection), we assessed the intercellular transfer and tissue penetration of Lucifer yellow, a gap junction-permeable (but membrane-impermeable) fluorescent tracer dye (Ruiz-Meana et al, 2001;Miura et al, 2004), in nine additional hearts. After stabilization, hearts received a 5-min infusion of heptanol or Gap 27 as described for protocol 2 or buffer alone (n ϭ 3/group).…”
Section: Protocol 3: Confirmation Of Gap Junction Inhibitionmentioning
confidence: 99%
“…The hearts were then rapidly removed from the apparatus and cut into five transverse slices. We used previously published methods (Ruiz-Meana et al, 2001;Miura et al, 2004) with minor modifications to introduce the dye into the myocardial slices and quantify fluorescence. Specifically, in the three slices obtained from the mid-myocardial region (apex and base discarded), shallow incisions were made on the epicardial surface at a uniform calibrated depth of 1 mm, thereby disrupting sarcolemmal membranes and allowing initial uptake of the membrane-impermeable dye.…”
Section: Protocol 3: Confirmation Of Gap Junction Inhibitionmentioning
confidence: 99%